Antenatal nutrition services offer in primary health care facilities of Kolda region, Senegal - Elhadji Alioune B Ningue; Isabelle Galibois; Sonia Blaney (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Both under and overnutrition have been associated with poor pregnancy outcomes. Hence, quality nutrition services are essential during pregnancy to help ensuring a healthy diet for expecting women especially in countries where malnutrition including anaemia is high, such as Senegal. Based on the Donabedian model of quality of care, the offer of nutrition services during antenatal care (ANC) was assessed in health facilities of Kolda region, Senegal. # Methods A cross-sectional descriptive survey was conducted among a random sample comprising 30% of the ANC providers of the region. Data on conditions and environment of health facilities were collected through direct observations as well as information on available equipment, materials and drugs/supplements. Data on ANC workforce such as their qualifications and supervision were gathered through a questionnaire. ANC providers were also asked to self-report their offer of nutrition services, including counseling. # Results With the exception of blood analyses equipment as well as calcium and energy-protein supplements, over 90% of health facilities had materials, equipment and supplies for providing nutrition services. ANC providers were either midwives or nurses as required by national standards but over 60% were not supervised every two months as prescribed. About 20% of them had received some training in maternal nutrition. Only 30% of ANC providers reported asking pregnant women about eating habits including the use of iodized salt, resting and sleeping habits and 15% on night blindness. Regarding nutrition counseling, 60% mentioned that they were always providing general dietary advice, 50% recommended specific foods to gain weight and 20% reported talking always about potential side effects of iron and folic acid supplementation. # Conclusions Although health providers have qualifications to perform ANC and work in a conducive environment, their capacities to provide nutrition services may be suboptimal. To some extent, this situation may contribute to the limited offer of nutrition services.